Drill point coating applied to printed circuit board and preparation method of drill point coating

By depositing tantalum powder on the surface of the ta-C coating, forming a composite coating with solar-grade polysilicon and carbon black, the problem of poor adhesion of the ta-C coating is solved, the hardness and friction resistance of the drilling needle are improved, and the thickness and friction resistance of the drilling needle are extended. Lifespan and enhanced stability.

CN119194357AActive Publication Date: 2024-12-27SHENZHEN HANS RUILI TIDE PRECISION COATING CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411613254.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2024-12-27
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The ta-C coating has poor adhesion due to its high hardness, resulting in a short wear life and it is difficult to maintain stability in high stress environments, affecting the service life of the drill needle.

Method used

The tantalum powder is mixed with solar-grade polycrystalline silicon and carbon black and then burned to form a composite, and the target is made into a hot press and deposited on the surface of the ta-C layer to form a composite coating to improve hardness and friction resistance and enhance adhesion.

Benefits of technology

By increasing the hardness and friction resistance of the composite coating, the service life of the drill needle is extended, the wear resistance and adhesion of the drill needle is improved, and the stability of the drill needle in high-stress environments is enhanced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of plating of metal materials, in particular to a drill point coating applied to a printed circuit board and a preparation method of the drill point coating. The preparation method comprises the following steps: S1, carrying out ion etching on the surface of a drill point; s2, continuously carrying out ion etching on the drill point by utilizing pulse negative bias; s3, pulse negative bias voltage is applied to the etched drill point, and a ta-C layer is obtained through a graphite target material; s4, a composite target material is obtained through tantalum powder, solar-grade polycrystalline silicon and carbon black; and S5, applying pulse negative bias, and depositing a composite layer on the ta-C layer by using the composite target material. The prepared drill point coating is high in hardness and strong in binding force, so that the service life of the drill point can be prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plating metal materials, and in particular to a drill needle coating applied to a printed circuit board and a preparation method thereof. Background Art

[0002] Printed circuit boards (PCBs) play an important role in many fields such as communications, industrial automation, automotive electronics, computers, consumer electronics, aerospace, and military electronics. As consumer electronics such as smartphones are moving towards thinner, lighter, and more multifunctional, PCB products are also moving towards smaller, finer, and more integrated, which has led to an increasing demand for micro-drilling technology. The micro-drilling process requires the use of drill bits with smaller diameters, especially micro-drills with a high aspect ratio. Drilling is a key step in the manufacturing process of PCBs. The drill bit rubs against the plate during high-speed rotation, generating high temperatures. At the same time, the notches formed during the processing will exert high stress on the cutting edge of the drill bit, causing fatigue or even breakage of the drill bit. The PCB industry consumes a lot of drill bits, so improving the durability of the drill bit has become a major challenge for manufacturers. Traditional tungsten carbide (WC) drill bits are widely used due to their excellent cost-effectiveness, but they are prone to breakage, which reduces the service life of the drill bit and increases the production cost of PCBs. To solve this problem, researchers are exploring coated drill bit technology. By applying surface engineering technology and coating a layer of special coating material on the cutting part of the drill bit, the drilling performance of the WC drill bit can be improved and its service life can be extended, thereby reducing production costs. Alternatively, surface nitriding (carbon), high-hardness nitride hard coating, and low-friction coefficient coating can be used to increase the service life of the drill bit.

[0003] Among them, ta-C coating (tetrahedral amorphous carbon) has been proven to be a surface treatment technology that can effectively increase the service life of micro-drills. Tetrahedral amorphous carbon, like diamond and graphite, is a carbon material with a structural composition between graphite and diamond. The ta-C coating is composed of carbon atoms, and its chemical structure is similar to that of diamond. 3 The bond content is more than 80%, and it has higher microhardness and thermal stability than ordinary DLC coatings. Generally, the wear resistance of a material is positively correlated with its hardness. Therefore, ta-C has better wear resistance than ordinary aC. In addition, since ta-C does not contain hydrogen and has high sp 3 -C content makes it have excellent thermal stability. In other words, ta-C should be more suitable than aC for the harsh conditions of modern industry such as high load, high speed, high temperature and long life. The thickness of ta-C coating used for drill bit is only a few hundred nanometers, which can achieve good protection effect and help to ensure the accuracy of drilling.

[0004] CN110343998A discloses a method for preparing a ta-C coating for a printed circuit board drill needle, comprising the following steps: 1) introducing a mixed gas of argon and hydrogen under vacuum conditions to etch the drill needle using an ion source; 2) ion etching the drill needle using argon gas with a negative bias voltage; 3) depositing a metal Cr bottom layer on the surface of the drill needle working surface; 4) applying a high pulse negative bias voltage to the drill needle to inject carbon atoms generated by a graphite target into the Cr bottom layer; 5) reducing the negative bias voltage to continue depositing carbon atoms to form a ta-C functional layer; the invention provides a ta-C coating for a printed circuit board drill needle and a preparation method thereof, which can increase the service life of the drill needle by 5-10 times, and can especially process ultra-thick printed circuit boards and high-hardness boards that are difficult to process with uncoated drill needles.

[0005] CN112267097A provides a composite coating for a printed circuit board drill and a preparation method thereof, wherein the composite coating includes a bottom layer, a carbonitriding layer, a diamond-like coating and a heat-insulating layer in order from the surface of the drill to the outside, wherein the bottom layer includes any one of a metal layer, an alloy layer or a metal compound layer, and the heat-insulating layer is a metal nitride ceramic layer. The composite coating of the present invention is designed with a multi-coating structure, wherein the setting of the diamond-like coating can effectively improve the hardness and wear resistance of the drill, thereby improving the service life of the drill, the setting of the carbonitriding layer can effectively improve the adhesion strength of the diamond-like coating, and avoid the problem that the diamond-like coating is easy to fall off, and the heat-insulating layer can delay the graphitization of the diamond-like coating, further improving the service life of the drill; the drill of the present invention is particularly suitable for drilling of high-frequency and high-speed printed circuit boards after the deposition of the composite coating, and the obtained drilling quality and precision are high.

[0006] However, due to its high hardness and internal stress, ta-C coating is not easy to adhere to the surface of the substrate material. High internal stress can easily cause the coating to crack or fall off, or cause severe deformation of the substrate, limiting the further thickness and practical application of the coating. Therefore, it is necessary to adopt co-doping or adding coating to improve the adhesion of the coating. However, this method will affect the wear resistance while improving the adhesion. Summary of the invention

[0007] In view of the above-mentioned defects in the prior art, the technical problem to be solved by the present invention is to provide a drill needle coating applied to a printed circuit board and a preparation method thereof.

[0008] The ta-C layer has a low friction coefficient, high chemical stability and wear resistance, and can significantly reduce the friction coefficient, adhesive wear and cutting force, so it is widely used as a coating for drill bits. However, it has a high hardness and poor adhesion to the surface of the drill bit, so the wear life is short. Therefore, the present invention obtains a composite by mixing tantalum powder with solar-grade polysilicon and carbon black and then burning them to synthesize the composite, and then hot-pressing them into a target material and depositing them on the surface of the ta-C layer. Since tantalum nitride and tantalum carbon are carbides and nitrides known for their high melting point, high hardness and high thermal stability, and the addition of silicon can not only improve the hardness and thermal stability, but also improve the oxidation resistance and friction resistance. Therefore, the drill bit coating obtained after the composite target material is deposited can have higher hardness and better friction resistance, so that the ta-C coating at the bottom can be protected, and the coating life will not be affected by its poor adhesion.

[0009] To achieve the above object, the present invention provides a method for preparing a drill needle coating for a printed circuit board, comprising the following steps: S1. A mixed gas of inert gas and hydrogen is introduced under vacuum to etch the surface of the drill needle; S2, continue to use the inert gas to ion etch the drill needle under the pulse negative bias voltage; S3, applying a pulsed negative bias voltage to the drill needle after etching, so that the graphite target material obtains a ta-C layer on the surface of the drill needle; S4, mixing tantalum powder with solar grade polysilicon and carbon black and then ball milling for mechanical activation, ball milling for 20-30 minutes, combustion synthesis at 3000-3500°C for 10-30 minutes, and then ball milling for 4-8 hours to obtain powder, adding the powder to 20% hydrochloric acid solution and heating for 4-6 hours to remove impurities, filtering, drying and hot pressing to obtain a composite target; S5. Using a mixture of nitrogen and argon, applying a pulsed negative bias voltage, and using a composite target material to deposit a composite layer on the ta-C layer in step S3, so as to obtain a drill needle coating.

[0010] Furthermore, the inert gas is argon.

[0011] Furthermore, the flow ratio of the inert gas to the hydrogen is 1:1~5sccm.

[0012] Furthermore, the negative bias voltage in step S2 is 100-300 V, and the duty cycle is 30-80%.

[0013] Furthermore, in step S3, the negative bias voltage is 100-400 V, the duty cycle is 30-80%, and the current of the graphite target is 40-80 A.

[0014] Furthermore, the mass ratio of the tantalum powder to solar-grade polysilicon and carbon black is 50-60:30-40:5-10.

[0015] Furthermore, the temperature range of the heating in step S4 is 70-80°C.

[0016] Furthermore, the hot pressing conditions are 1500-1800° C., 20-40 MPa, and 5-15 min.

[0017] Furthermore, in step S5, the flow ratio of nitrogen to argon is 1:1~10sccm, the negative bias voltage is 100~500V, the duty cycle is 30~80%, and the current of the composite target is 50~80A.

[0018] The present invention also provides a drill needle coating applied to a printed circuit board, which is prepared by the above method.

[0019] Beneficial effects of the present invention: The present invention obtains a composite by mixing tantalum powder with solar-grade polysilicon and carbon black, and then burning and synthesizing the mixture, and then hot pressing the mixture into a target material and depositing it on the surface of the ta-C layer. Since tantalum nitride and tantalum carbon are carbides and nitrides known for their high melting point, high hardness and high thermal stability, and the addition of silicon can not only improve the hardness and thermal stability, but also improve the oxidation resistance and friction resistance, the drill bit coating obtained after the composite target material is deposited can have higher hardness and better friction resistance, thereby protecting the bottom ta-C coating, and will not affect the coating life due to its poor adhesion. DETAILED DESCRIPTION

[0020] Tantalum powder, purity: 3N grade, Zhuozhou Yourong New Material Technology.

[0021] Solar-grade polysilicon, Shandong Ruiyang Silicon Technology.

[0022] Carbon black, N-330, Shandong Kepler Biotechnology.

[0023] Example 1 A method for preparing a drill needle coating for a printed circuit board comprises the following steps: S1. A mixed gas of argon and hydrogen is introduced under vacuum to etch the surface of the drill needle, and the flow ratio of argon to nitrogen is 1:2 sccm; S2, continue to use argon gas to ion etch the drill needle under a pulsed negative bias voltage of 200V, with a duty cycle of 30%; S3, applying a pulsed negative bias voltage of 400V to the drill bit after etching, with a duty cycle of 50%, so that the graphite target obtains a ta-C layer on the surface of the drill bit, and the target current is 60A; S4, mixing tantalum powder with solar-grade polysilicon and carbon black in a mass ratio of 53.5:37.5:9, and then ball milling for mechanical activation, ball milling for 20 minutes, combustion synthesis at 3500° C. for 20 minutes, and then ball milling for 6 hours to obtain powder, adding the powder to 20% hydrochloric acid and heating it to 80° C. for 5 hours to remove impurities, filtering, drying, and hot pressing at 1600° C. and 30 MPa for 10 minutes to obtain a composite target; S5. Nitrogen and argon are mixed at a flow ratio of 1:5 sccm, a pulsed negative bias of 450 V is applied, and a duty cycle of 60% is applied. A composite layer is deposited on the ta-C layer in step S3 using a composite target. The current of the composite plate is 80 A, and a drill needle coating is obtained.

[0024] Example 2 A method for preparing a drill needle coating for a printed circuit board comprises the following steps: S1. A mixed gas of argon and hydrogen is introduced under vacuum to etch the surface of the drill needle, and the flow ratio of argon to nitrogen is 1:2 sccm; S2, continue to use argon gas to ion etch the drill needle under a pulsed negative bias voltage of 200V, with a duty cycle of 30%; S3, applying a pulsed negative bias voltage of 400V to the drill bit after etching, with a duty cycle of 50%, so that the graphite target obtains a ta-C layer on the surface of the drill bit, and the target current is 60A; S4, mixing tantalum powder with solar grade polysilicon and carbon black in a mass ratio of 60:30:10 and then ball milling for mechanical activation, ball milling for 20 minutes at 3500°C for 20 minutes, and then ball milling for 6 hours to obtain powder, adding the powder to 20% hydrochloric acid and heating it to 80°C for 5 hours to remove impurities, filtering, drying, and hot pressing at 1600°C and 30MPa for 10 minutes to obtain a composite target; S5. Nitrogen and argon are mixed at a flow ratio of 1:5 sccm, a pulsed negative bias of 450 V is applied, and a duty cycle of 60% is applied. A composite layer is deposited on the ta-C layer in step S3 using a composite target. The current of the composite plate is 80 A, and a drill needle coating is obtained.

[0025] Example 3 A method for preparing a drill needle coating for a printed circuit board comprises the following steps: S1. A mixed gas of argon and hydrogen is introduced under vacuum to etch the surface of the drill needle, and the flow ratio of argon to nitrogen is 1:2 sccm; S2, continue to use argon gas to ion etch the drill needle under a pulsed negative bias voltage of 200V, with a duty cycle of 30%; S3, applying a pulsed negative bias voltage of 400V to the drill bit after etching, with a duty cycle of 50%, so that the graphite target obtains a ta-C layer on the surface of the drill bit, and the target current is 60A; S4, mixing tantalum powder with solar grade polysilicon and carbon black in a mass ratio of 50:40:10 and then ball milling for mechanical activation, ball milling for 20 minutes, combustion synthesis at 3500° C. for 20 minutes, and then ball milling for 6 hours to obtain powder, adding the powder to 20% hydrochloric acid and heating it to 80° C. for 5 hours to remove impurities, filtering, drying, and hot pressing at 1600° C. and 30 MPa for 10 minutes to obtain a composite target; S5. Nitrogen and argon are mixed at a flow ratio of 1:5 sccm, a pulsed negative bias of 450 V is applied, and a duty cycle of 60% is applied. A composite layer is deposited on the ta-C layer in step S3 using a composite target. The current of the composite plate is 80 A, and a drill needle coating is obtained.

[0026] Example 4 A method for preparing a drill needle coating for a printed circuit board comprises the following steps: S1. A mixed gas of argon and hydrogen is introduced under vacuum to etch the surface of the drill needle, and the flow ratio of argon to nitrogen is 1:2 sccm; S2, continue to use argon gas to ion etch the drill needle under a pulsed negative bias voltage of 200V, with a duty cycle of 30%; S3, applying a pulsed negative bias voltage of 400V to the drill bit after etching, with a duty cycle of 50%, so that the graphite target obtains a ta-C layer on the surface of the drill bit, and the target current is 60A; S4, mixing tantalum powder with solar grade polysilicon and carbon black in a mass ratio of 55:40:5 and then ball milling for mechanical activation, ball milling for 20 minutes, combustion synthesis at 3500°C for 20 minutes, and then ball milling for 6 hours to obtain powder, adding the powder to 20% hydrochloric acid and heating it to 80°C for 5 hours to remove impurities, filtering, drying, and hot pressing at 1600°C and 30MPa for 10 minutes to obtain a composite target; S5. Nitrogen and argon are mixed at a flow ratio of 1:5 sccm, a pulsed negative bias of 450 V is applied, and a duty cycle of 60% is applied. A composite layer is deposited on the ta-C layer in step S3 using a composite target. The current of the composite plate is 80 A, and a drill needle coating is obtained.

[0027] Comparative Example 1 A method for preparing a drill needle coating for a printed circuit board comprises the following steps: S1. A mixed gas of argon and hydrogen is introduced under vacuum to etch the surface of the drill needle, and the flow ratio of argon to nitrogen is 1:2 sccm; S2, continue to use argon gas to ion etch the drill needle under a pulsed negative bias voltage of 200V, with a duty cycle of 30%; S3. Apply a pulsed negative bias voltage of 400V to the drill bit after etching with a duty cycle of 50%, so that the graphite target material obtains a ta-C layer on the drill bit surface. The target current is 60A, and the drill bit coating is obtained.

[0028] Test Example 1 The nanohardness of the coatings of the embodiment and the control example was tested by the indentation method using a nanoindenter, with an indentation load of 8 mN to ensure that the indentation depth was less than 1 / 10 of the film thickness, and the test mode was a continuous stiffness mode. During the test, 6 smooth and uncontaminated areas were randomly selected to test the hardness, and the average value was calculated to obtain the nanohardness value.

[0029] Table 1 Hardness of drill tip coatings used in printed circuit boards Experimental protocol Nanohardness / GPa Example 1 38.9 Example 2 37.6 Example 3 38.1 Example 4 36.9 Comparative Example 1 27.4 By comparing the control example with the embodiment, it can be found that when the composite layer is not deposited on the surface of the ta-C layer, the hardness of the drill bit coating obtained is significantly worse. This is because tantalum nitride and tantalum carbon are carbides and nitrides known for their high melting point, high hardness and high thermal stability, and the addition of silicon can further improve the hardness. Therefore, the deposited composite coating can give the drill bit higher mechanical properties, so the hardness is greater than that of the control example 1 without the composite coating. The difference between Examples 1 to 4 shows that tantalum powder, solar-grade polysilicon and carbon black will affect the performance of the final composite coating. From the results, the ratio in Example 1 is better.

[0030] Test Example 2 The scratch method is used to characterize the bonding strength between the coating and the drill needle of the embodiment and the control example. During the test, the conical indenter is scratched on the coating for a certain distance at a certain speed, and the vertical pressure acting on the indenter is gradually or continuously increased until the coating peels off. When the coating is subjected to vertical pressure, it will experience two important load stages: the vertical load when the coating begins to crack is called the first critical load; and the vertical load when the coating first peels off obviously is called the second critical load. Since the initial formation position of the coating crack is usually difficult to observe, the second critical load is regarded as an indicator of the bonding strength between the coating and the substrate. In order to test the bonding performance of the coating and the substrate, the scratch module of the friction tester is used. The experimental setting is as follows: the vertical load is gradually increased from 0 to 1N and maintained at this load for 10s. Subsequently, within 15s, the load is gradually increased from 1N to 30N, while a sliding displacement of 10mm is performed. The above experimental steps are repeated three times for each sample. Since the load increases linearly with the sliding distance, each point in the sliding process corresponds to a specific pressure value. By analyzing the relationship between load and displacement, the second critical load is obtained.

[0031] Table 2 Bonding strength of drill tip coating applied to printed circuit boards Experimental protocol The second critical load / N Example 1 25.4 Example 2 23.2 Example 3 24.1 Example 4 22.3 Comparative Example 1 13.8 By comparing the control example with the embodiment, it can be found that the drill bit coating prepared in the embodiment has a stronger bonding force with the drill bit surface. This may be because the ta-C coating in the control example 1 is harder but more brittle, and has a lower ability to resist plastic deformation under the action of vertical stress, resulting in earlier peeling. The addition of silicon in the embodiment improves the anti-friction performance of the composite coating, so the coating is less likely to peel off when facing vertical stress, and the bonding strength between the coating and the drill bit surface is better.

[0032] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A method for preparing a drill needle coating for a printed circuit board, characterized in that: The steps include: S1. A mixed gas of inert gas and hydrogen is introduced under vacuum to etch the surface of the drill needle; S2, continue to use the inert gas to ion etch the drill needle under the pulse negative bias voltage; S3, applying a pulsed negative bias voltage to the drill needle after etching, so that the graphite target material obtains a ta-C layer on the surface of the drill needle; S4, mixing tantalum powder with solar grade polysilicon and carbon black and then ball milling for mechanical activation, ball milling for 20-30 minutes, combustion synthesis at 3000-3500°C for 10-30 minutes, and then ball milling for 4-8 hours to obtain powder, adding the powder to 20% hydrochloric acid solution and heating for 4-6 hours to remove impurities, filtering, drying and hot pressing to obtain a composite target; S5. Using a mixture of nitrogen and argon, applying a pulsed negative bias voltage, and using a composite target material to deposit a composite layer on the ta-C layer in step S3, so as to obtain a drill needle coating.

2. The method for preparing a drill needle coating for a printed circuit board according to claim 1, characterized in that: The inert gas is argon.

3. The method for preparing a drill needle coating for a printed circuit board according to claim 1, characterized in that: The flow ratio of the inert gas to the hydrogen is 1:1-5 sccm.

4. The method for preparing a drill needle coating for a printed circuit board according to claim 1, characterized in that: The negative bias voltage in step S2 is 100-300V, and the duty cycle is 30-80%.

5. The method for preparing a drill needle coating for a printed circuit board according to claim 1, characterized in that: The negative bias voltage in step S3 is 100-400 V, the duty cycle is 30-80%, and the current of the graphite target is 40-80 A.

6. The method for preparing a drill needle coating for a printed circuit board according to claim 1, characterized in that: The mass ratio of the tantalum powder to solar-grade polysilicon and carbon black is 50-60:30-40:5-10.

7. The method for preparing a drill needle coating for a printed circuit board according to claim 1, characterized in that: The temperature range of the heating in step S4 is 70-80°C.

8. The method for preparing a drill needle coating for a printed circuit board according to claim 1, characterized in that: The hot pressing conditions are 1500-1800° C., 20-40 MPa, and 5-15 min.

9. The method for preparing a drill needle coating for a printed circuit board according to claim 1, characterized in that: In the step S5, the flow ratio of nitrogen to argon is 1:1-10 sccm, the negative bias voltage is 100-500 V, the duty cycle is 30-80%, and the current of the composite target is 50-80 A.

10. A drill needle coating for a printed circuit board, characterized in that: Prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • TaC-SiC ceramic composite material synthesized by hot pressing at in-situ reaction and synthetic method thereof

    CN101417878A

  • Printed circuit board drill needle ta-C coating and preparation method thereof

    CN110343998A

  • Low-stress tetrahedral amorphous carbon composite film and preparation method thereof

    CN111005000A

  • Preparation method of transition metal refractory compound ceramic composite coating

    CN111334742A

  • Composite coating of printed circuit board drill point and preparation method thereof

    CN112267097A